a=(-5)+(-17)+(-15)+(-17)-17-(-2)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a,-5/9 + 8/18 + -2/11 + 4/-9 + 7/15 b,5/17 + -9/15 + -2/17 + 2/5 + 14/17
= -5/9 + 4/9 + -2/+ 4/-9 + 7/15 = 5/17 + -3/5 + -2/17 + 2/5 + 14/17
=(-5/9 + 4/9 + -4/9 ) +-2/11 + 7/15 = ( 5/17 + -2/17 + 14/17) + ( 2/5 + -3/5)
= -1/3 + -2/11 + 7/15 =1 + -1/5
=-75/225 + -30/ 225 + 77/225 =4/5
= -25/225 = -1/9 ( 4/5 = 0.8 )
ta có:\(A=\frac{17^{15}+3}{17^{15}-2}=\frac{17^{15}-2+5}{17^{15}-2}=\frac{17^{15}-2}{17^{15}-2}+\frac{5}{17^{15}-2}=1+\frac{5}{17^{15}-2}\)
\(B=\frac{17^{15}}{17^{15}-5}=\frac{17^{15}-5+5}{17^{15}-5}=\frac{17^{15}-5}{17^{15}-5}+\frac{5}{17^{15}-5}=1+\frac{5}{17^{15}-5}\)
vì 1715-2>1715-5
=>\(\frac{5}{17^{15}-2}<\frac{5}{17^{15}-5}\)
=>A<B
1: \(=-145\cdot13+145\cdot57+57\cdot10-57\cdot145=-1315\)
2: \(=17\cdot15-17\cdot16+16\cdot17-16\cdot20=255-320=-65\)
3: \(=-38\cdot25+38\cdot4-25\cdot4+25\cdot38=13\cdot4=52\)
4: \(=23\cdot145-23\cdot17-145\cdot23+145\cdot6=479\)
5: \(=24\cdot15-24\cdot4+4\cdot24-4\cdot15=360-60=300\)
6: \(=199\left(15-17+17-5\right)=199\cdot10=1990\)
7: \(=-39\cdot5+39\cdot99+99\cdot10-99\cdot39=795\)
Lời giải chi tiết:
12 – 2 < 11 | 13 > 17 – 5 | 18 – 8 = 11 – 1 |
15 – 5 < 15 | 17 > 19 – 5 | 17 – 7 = 12 – 2 |
a: =35/17-18/17-9/5+4/5
=1-1=0
b: =-7/19(3/17+8/11-1)
=7/19*18/187=126/3553
c: =26/15-11/15-17/3-6/13
=1-6/13-17/3
=7/13-17/3=-200/39
\(A=-5-17-15-17-17+2\)
\(A=-71+2=-69\)
A=(-5)+(-17)+(-15)+(-17)-17-(-2)
=>A=-5-17-15-17-17-2
=>A= -(5+17+15+17+17+2)
=> A= -73